ANALYSIS, DESIGN AND IMPLEMENTATION OF AN EMBEDDED REALTIME SOUND SOURCE LOCALIZATION SYSTEM BASED ON BEAMFORMING THEORY - Arko Djajadi; Rusman Rusyadi; Tommy Handoko; Maralo Sinaga; Jürgen Grueneberg (Universitas Ahmad Dahlan, 2009)
This project is intended to analyze, design and implement a realtime sound source localization system by using a mobile robot as the media. The implementated system uses 2 microphones as the sensors, Arduino Duemilanove microcontroller system with ATMega328p as the microprocessor, two permanent magnet DC motors as the actuators for the mobile robot and a servo motor as the actuator to rotate the webcam directing to the location of the sound source, and a laptop/PC as the simulation and display media. In order to achieve the objective of finding the position of a specific sound source, beamforming theory is applied to the system. Once the location of the sound source is detected and determined, the choice is either the mobile robot will adjust its position according to the direction of the sound source or only webcam will rotate in the direction of the incoming sound simulating the use of this system in a video conference. The integrated system has been tested and the results show the system could localize in realtime a sound source placed randomly on a half circle area (0 - 1800) with a radius of 0.3m - 3m, assuming the system is the center point of the circle. Due to low ADC and processor speed, achievable best angular resolution is still limited to 25o.